The Effect of Destination Image, Tourist Attractions, Facilities, Service Quality, and Promotion on Visitor Satisfaction at Telagah Kumpe Cilongok Tourist Destination - Indra Saputra; Sugeng Rianto (International Research & Development for Human Beings (IRDH), 2025)
This study aims to examine the destination image, tourist attractions, facilities, service quality, and promotion on visitor satisfaction. The method used is a quantitative approach with descriptive analysis techniques. Purposive Sampling, involving 220 samples. Data were obtained through questionnaire distribution and analyzed using Smart PLS V.4.1. The results of the study showed that: (1) destination image has a positive effect on visitor satisfaction, (2) tourist attractions have a positive effect on visitor satisfaction, (3) facilities do not have an effect on visitor satisfaction, (4) service quality has a positive effect on visitor satisfaction, (5) promotion has a positive effect on visitor satisfaction. This study concludes that destination image, tourist attractions, service quality, and promotions have a positive effect on visitor satisfaction at Telaga Kumpe, while facilities were not shown to have a significant effect. This means that tourist satisfaction is largely determined by how the destination is perceived, the attractions offered, the services provided, and the promotional strategies employed